Modulation of macrophage activation by prostaglandins - L. Sautebin; R. Carnuccio; F. D'Acquisto; M. Di Rosa (Mediators of Inflammation)
The effect of prostaglandtn E2, iloprost and cAMP on both nitric oxide and tumour necrosis factor-α release in J774 macrophages has been studied. Both prostaglandin E2 and iloprost inhibited, in a concentration-dependent fashion, the lipopolysaccharide-induced generation of nitric oxide and tumour necrosis factor-α. The inhibitory effect of these prostanoids seems to be mediated by an increase of the second messenger cAMP since it was mimicked by dibutyryl cAMP and potentiated by the selective type IV phosphodiesterase inhibitor RO-20-1724. Our results suggest that the inhibition of nitric oxide release by prostaglandin E2 and iloprost in lipopolysaccharide-activated J774 macrophages may be secondary to the inhibition of tumour necrosis factor-α generation, which in turn is likely to be mediated by cAMP.